A comparative study for the performance operation of electric machine based on conventional and D-Q theories - Sanabel M. AL hajzber; Ahmed J. Ali; Alya H. AL-Rifaie; Abdullah K. Shanshal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Induction motors are used widely in industrial applications, thanks to their high efficiency and reliability which nominates it as a good machine used in various application. Based on the application and accuracy, modeling processes of electric machines are carried out using different mathematical methods. The most common method for modeling electrical machines is based on solution of differential equations of voltages as well as calculating the time varying self-inductances and the mutual inductances based on the rotor angle. One of the most important features of this method is that the inductance is no long depend on the time varying voltage, which is the major problem facing the conventional model. But the D-Q modeling approach has several problems, the greatest of which is that the voltage applied on stator must be balanced in addition to the fact that the winding are sinusoidal distributed form. Herein this research is focused on build two models of a 3-Φ induction motor (IM) based on the two analytical approaches and compare them to clarify the difference. The results have been shown that the conventional model gives more accurate response when it is applied in both normal and upnormal operation. MATLAB/Simulink softare is used to construct the D-Q and classical abc IM models.